2017
DOI: 10.4236/ojl.2017.62005
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Relationship between Transformational Leadership and Government Service Innovation

Abstract: In this research, the thinking is carried out in accordance with logical order. The results of this study show that: the four dimensions of transformational leadership have different effects on the service innovation of government departments. On the basis of the results, this paper puts forward four specific strategies and methods to achieve and improve the service innovation of government departments, and discusses the shortcomings of this study and future research directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…However, research on this topic remains immature (Seeck and Diehl, 2017; Tajeddini et al , 2020) and empirical studies that concentrate on this topic remain scarce (Fu et al , 2015; Sanz-Valle and Jiménez-Jiménez, 2018) particularly in the government sector (Escribá-Carda et al , 2017; Prieto and Perez-Santana, 2014). Studies have stressed the need to investigate this relationship in such organisations (Seeck and Diehl, 2017), Studies have stressed the need to investigate this relationship in such organisations (Seeck and Diehl, 2017), in light of lack of academic attention (Chen and Peng, 2017) and weak interest of government organisations in this topic (Tether, 2005). In addition, studies suggested conducting service innovation research in different countries and various service industries (Kuo et al , 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, research on this topic remains immature (Seeck and Diehl, 2017; Tajeddini et al , 2020) and empirical studies that concentrate on this topic remain scarce (Fu et al , 2015; Sanz-Valle and Jiménez-Jiménez, 2018) particularly in the government sector (Escribá-Carda et al , 2017; Prieto and Perez-Santana, 2014). Studies have stressed the need to investigate this relationship in such organisations (Seeck and Diehl, 2017), Studies have stressed the need to investigate this relationship in such organisations (Seeck and Diehl, 2017), in light of lack of academic attention (Chen and Peng, 2017) and weak interest of government organisations in this topic (Tether, 2005). In addition, studies suggested conducting service innovation research in different countries and various service industries (Kuo et al , 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Este tipo de líder partilha a sua visão de futuro. Pode ser caracterizado como sendo um líder corajoso, enorme impulsionador de valores pessoais pois acredita na capacidade das pessoas, possui um enorme desejo de aprendizagem constante, não receando ter de lidar de forma ambiciosa e coerente com a complexidade, ambiguidade e incerteza (WALDMAN; YAMMARINO, 1999;BARRACHO, 2012;CHEN;PENG, 2017;REIS, 2019).…”
Section: Liderança Transformacionalunclassified
“…et al, 2019). É o tipo de liderança que se distância largamente de uma liderança autoritária, ao mesmo tempo que transcende o próprio conceito de liderança democrática, isto é, a liderança transformacional é o tipo de liderança que procura não só democratizar processos, mas cujo foco principal está nas pessoas e no seu desenvolvimento ao mesmo tempo que se tenta atingir resultados de excelência (AVOLIO et al, 2004;BARRACHO, 2012;CUNHA et al, 2016;CHEN;PENG, 2017). Resultados esses por vezes nunca alcançados, recorrendo a elevados níveis de motivação, entrega e desempenho em que as próprias pessoas se sentem estimuladas a ir mais além.…”
Section: Caracterização Da Amostraunclassified
“…The unanimous consensus of successful management that creativity is one of the main factors for success, performance, and productivity (Rodríguez-Pose et al, 2020). It also positively impacts earnings, growth, and market shares of organizations (Ardito et al, 2017;Akbari and Monzavi, 2015) growth of jobs (Bonfanti et al, 2018;Chen and Peng, 2017); return on assets and growth of sales (Chang and Lee, 2020;Mulgan and Albury, 2003). Innovation is also pushing organizations to retain their strategic place and excellence in a turbulent and competitive world (Gaynor, 2002;Leal-Rodríguez et al, 2015).…”
Section: Human Capital and Service Innovationmentioning
confidence: 99%
“…The tourism industry is one of the most industrial sectors driving the global economy at the present time (Bazazo and Alananzeh, 2020). Many service organizations have recently focused on how to improve their employees' operation, enhance quality services, and increase their market share through encouraging initiatives and innovation activities (Alosani et al, 2020;Chen, 2018;Chen and Peng, 2017). One of the bases on which institutions depend is an investment in innovation because the demand for goods and services is constantly fluctuating and there are horizontal and vertical implications for organizations and changing the patterns of the target market and the economic situation of societies, so the economic returns of innovation exceed the fixed returns in traditional management (Chang and Lee, 2020;Stojcic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%